Места отправления религиозных культов в Херсонесе Таврическом и его округе в эллинистический период - Зубарь, В.М. (Материалы по археологии, истории и этнографии Таврии, 2005)
The article examines the places of serving religious cults on the bases of archaeological and epigraphic data. In Chersonesos those cults were served publicly at the temples, or home sanctuary. On the basis of disposable sources we can assert that in Chersonesos of Hellenistic period cult activities in the honour of gods- pfotectors were performed in the same way as in other regions of ancient world. Sacred cults in the honour of gods were exercised near the temples by the majority of members of community, and at home by small groups. It is known that both religious acts should be regarded as inseparably linked, which was a characteristic feature of religious ideology of the population of Chersonesos. From the Зrd century B.C. we can observe the beginning of transformation of religious representations of Chersonesos population connected with the crisis of polis ideology. However, this tendency in Chersonesos became apparent only in the first centuries A.D.